Mobile Social Networking An Innovative Approach - Chin, Alvin; Zhang, Daqing; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The use of contextually aware, pervasive, distributed computing, and sensor networks to bridge the gap between the physical and online worlds is the basis of mobile social networking. This book shows how applications can be built to provide mobile social networking, the research issues that need to be solved to enable this vision, and how mobile social networking can be used to provide computational intelligence that will improve daily life. With contributions from the fields of sociology, computer science, human-computer interaction and design, this book demonstrates how mobile social networks can be inferred from users' physical interactions both with the environment and with others, as well as how users behave around them and how their behavior differs on mobile vs. traditional online social networks.
1. Introduction -- 2. Socially Aware Computing: Concepts, Technologies, and Practices -- 3. Ephemeral Social Networks -- 4. Social Behavior in Mobile Social Networks: Characterizing Links, Roles and Communities -- 5. Mobile Social Service Design for Special Context -- 6. Exploiting Personal and Community Context in Mobile Social Networks -- 7. Enhancing Mobile Social Networks with Ambient Intelligence -- 8. Data Analysis on Location-Based Social Networks -- 9. Towards Trustworthy Mobile Social Networking -- 10. Conclusions.
Keywords: Physics; Computer Communication Networks; Computer science; Engineering; Telecommunication; Physics; Complex Networks; Computer Communication Networks; Communications Engineering, Networks; Communication Studies; Complexity; User Interfaces and Human Computer Interaction